Strategi Penyebaran Produk yang Efektif dengan Menggunakan Analisis Biaya dan Laba - Dwi Nurul Azizah; Muhamad Ariel Rakhadian; Muhammad Hisyam Trinugraha; Naila Rahma; Wilda Fahriah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Product distribution is one of the most important components of a marketing strategy, directly impacting the achievement of sales targets and the competitiveness of an SME in the market. In an increasingly competitive era, the success of a product in the market is not only determined by quality but also by how effectively the product can be distributed widely and precisely to consumers. The main challenge often faced by Kabita Cookies SMEs is in developing an effective and efficient product distribution strategy. Many SMEs do not yet understand how to design a distribution strategy that considers cost and profit aspects. This community service activity aims to provide guidance on the importance of an effective and efficient product distribution strategy using cost and profit analysis as an effort to increase sales and market share. This activity also directly involves several SME practitioners to help SMEs understand the best guidance in distributing a product effectively and measurably. This study uses a quantitative method with data collection through interviews, surveys, and observations. The results of the study show an increase in SMEs' understanding of product distribution and cost and profit analysis. Kabita Cookies SMEs can increase sales and market share by implementing effective and efficient product distribution strategies, such as selecting the right distribution channels, collaborating with distribution partners, and utilizing digital platforms. This program is expected to continue contributing to SME development and product marketing capabilities. This activity is expected to be implemented in SMEs on an ongoing basis to improve marketing quality and increase sales in the market.